(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The medicinal plant species diversity of the National Nature Park “Tuzlovski lymany” consists of 403 species from 76 families. It’s 70,5 % of the total flora of the park and almost twice the proportion of medicinal plants in the Ukrainian flora (37 %). Families Lamiaceae (94,7 %), Brassicaceae (93,3 %), Apiaceae (87,5 %) and Asteraceae (74,0 %) are especially rich in medicinal plants. The annuals and biennials are dominated among the life forms (184 species, 45,7 %), there are 155 herbaceous perennials (15,8 % less). The proportion of woody plants is 12,7 % (51 species). Anthropophyton is the richest florotsenotype (130 species), followed by Steppophyton (98 species, 23.8%), Drymophyton is the third (74 species, 18,4 %). Medicinal flora of the NNP “Tuzlovski lymany” includes 47 officinal, 269 non-officinal and 87 potential medicinal species. The underground plant organs are medicinal plant material of nearly a fifth of all the plants (17,6 %), 68,7 % medicinal plants gives “herb” as medicinal material. Species with non-commercial reserves are dominated (228 species, 56,6 %), 137 species (34,0 %) don’t have reserves, reserves of 24 protected species aren’t available (6,0 %). Researves of 13 species are described as commercial. Two officinal species (Matricaria recutita, Conium maculatum) have commercial researves, 31 – non-commercial, 5 species havn’t researves, researves of two species aren’t available. The limitations in medicine plant collection are detailed in the park.